A Note on Optimal Depreciation Research–A Comment. - Osteryoung, Jerome S.; McCarty, Daniel E.; Fortin, Karen (The Accounting Review, 1981)
Abstract In this article the authors comment on a note by researcher Clyde P. Stickney on optimal tax depreciation choice. It is Stickney's belief that the refinements made in the original model should be published in professional journals rather than academic journals. He is critical of the use of only partially rather than completely specified decision models in these various research efforts. He also suggests that an earlier note by the authors contains several errors. Stickney also argues that the effects of changes in the tax laws are of interest again only to the practitioner. One need look at only a few academic journals to see that the effects of changes in accounting standards, regulations by the U.S. Securities Exchange Commission, and auditing practices are of acute interest to academicians. Stickney identified what he believed to be three errors in a prior work by the authors. The first two, the optimal switchover year and the depreciation deductions taken, are interrelated and are valid points of criticism. The third criticism of the interpretation of salvage value is totally in error, however.